PERAN SISTEM DALAM MENJAGA ASET PALING BERHARGA UNIVERSITAS: Studi Kasus Pada Universitas Airlangga - Jeffits Khusnu Alif; Noorlaily Sewarno; Isnalita (Universitas Methodist Indonesia, 2019)
This research focuses on the status of the lecturer as the foundation of a University , because the have the responsibility to educating a new generation that could bring pride to University, so there is no doubt that lecturer could be called the most valuable asset of the University (Ramírez Córcoles, Santos Peñalver, & Tejada Ponce, 2011; Suyunus, 2011; Ulum, 2012). This research is a case study research with intepretif paradigm, which aim to determine the extent to which the result of a student evaluation of lecturer that measured by Airlangga University cybercampus questionnaires used as references by it’s lecturer and faculty.